An Investigation Into Students' Writing Difficulties. Case of Second Year LMD Classes - Mohamed Lokmane, BOUCHIBI (My University, 2018)
Abstract Written expression in foreignlanguageisamong the mostcomplex practices for English languagestudents. This isbecausewritingis one of the mostdifficultlanguageskills in terms of learningbecauseitrequiresa lot of effort and practice fromstudents to reach a good level. Most students have difficulties in writingaspecifictext about anytopic. Therefore, thisstudyintends the variousproblems writing faced by second-yearstudents in English. The aim of thisstudyis to see if the studentfollow the steps of writing, sincewritingitselfis a follow-up to manycomplexproceduresthat the student must follow in writing. Consequently, in order to arrive to prove the study's content regarding the variousdifficultiesfaced by English second year students, weconductedtwosurveys, the first wasdevoted to teacherswithexperience in teaching English written expression, and the other to second yearstudentsat the University of Mohammed Boudiaf M'sila.Therefore, weprepared a number of suggestions in orderovercome the variousdifficultiesthrough the results of both questionnaires given to bothteachers and students.
Keywords: Key Words : Writing difficulties, students, second year, LMD, investigation, linguistic, congnitive, psychological, pedagogical.